Критическое мышление как фактор профессиональной компетентности программистов - Юлия Андреевна Кукушкина; Владимир Феликсович Спиридонов (Психология. Журнал Высшей школы экономики, 2011)
The phenomenon of «critical thinking» understood as a complex of inter-related metacognitive (heuristic) strategies is analyzed. The results of empirical study of critical thinking impact on the success of professional problem solving by «experts» and «novices» in the programming domain are outlined. It is shown that critical thinking is closely connected to the success of professional problem solving and that this effect is provided by the metacognitive strategies which constitute critical thinking.  The differences between experts and novices are revealed which lie in the intensity and sustainable use of metacognitive strategies by the experts in the significant situations of difficulties (so-called «points of inflection»).